ANTHROPOZOOLOGY'S ARCHITECTURE: ANIMAL CENTER TO SUPPORT ANIMAL AND HUMAN RELATIONSHIPS THROUGH INTERACTION - Aulia Kinanti, Zahra
Animal violence is a form of crime committed by humans against animals for purposes other than self-protection. However, based on the Social Media Animal Cruelty Coalition (SMACC) report, Indonesia actually has the highest level of animal cruelty in the world. This is also supported by the existence of various news related to violence against animals in Indonesia, including Jakarta. This is something that is urgent to deal with in order to create a safe and comfortable environment for all living things. Responding to the existing issues and conditions, a place is needed to accommodate these activities which include education and recreation. Therefore, the Animal Center was designed with educational and recreational functions based on interactions between animals and humans. The project is located in an area that is known by many for its connection to animals, both from the existence of a zoo or pet shop around it, it is located in JL. Ampera Raya, Ragunan, Pasar Minggu, City of South Jakarta, Special Capital Region of Jakarta, with a maximum land size of ±7,500 m². The location also has good accessibility, and is close to various schools and housing to support its educational and recreational functions. The design issue consists of three main aspects, namely designing an Animal Center that has a restorative function with a biophilic design approach to provide a feeling of comfort, designing an Animal Center with a good level of permeability and spatial flexibility to accommodate organizational and/or community activities related to animals, as well as designing Animal Centers that are interactive between animals and humans to provide positive new experiences, which can also be a non-formal educational forum to increase human bonding and knowledge of animals. To support its aspects, the Animal Center is designed by open spaces, and the spaces that are made can be seen from the outside. The interactive approach was chosen because it is proven to be able to foster bonding and create a paradigm shift to people, where it can increase human awareness of animals and reduce existing animal violence.